The Influence of Age and Educational Background on Teachers’ Participation in Decision-Making at Islamic Junior High Schools in Makassar - Rosmiati Rosmiati; Bisyri Abdul Karim; Akhmad Syahid (STAI Hubbulwathan Duri, 2025)
This study examines the influence of teachers’ age and educational background on their participation in decision-making at State Islamic Junior High Schools (Madrasah Tsanawiyah Negeri) in Makassar City. Specifically, it investigates how these two demographic factors (independent variables) affect the level of teacher involvement in institutional decision-making processes (dependent variable). A correlational survey design was employed to explore these relationships. The population comprised 135 teachers from two MTsN schools in Makassar, and a sample of 67 teachers was selected using Arikunto’s (1991) sampling guidelines. Data were collected through a structured questionnaire measuring six indicators of participation—problem identification, problem formulation, development and selection of alternatives, implementation, and evaluation. Descriptive statistics were used to profile respondents by age and educational attainment, while inferential analyses, including partial correlation and multiple regression, were conducted using SPSS. Results show that 28% of respondents were aged 24–30, 36.7% aged 31–37, and the remainder distributed across older age groups; 80% held a bachelor’s degree, with smaller proportions holding diplomas or master’s degrees. Both age and educational level were found to have a positive and statistically significant influence on teacher participation in decision-making. Older and more highly educated teachers demonstrated greater involvement, reflecting higher cognitive maturity and analytical ability. These findings highlight the importance for school leaders and policymakers of considering demographic factors when promoting participatory decision-making. Tailored professional development and inclusive governance structures may enhance teachers’ engagement and improve institutional decision-making quality.